2021
DOI: 10.1177/08862605211037433
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Burden of Intimate Partner Violence by Sex and Sexual Identity: Results From a Random Sample in Toronto, Canada

Abstract: Debates on how sex, gender, and sexual identity relate to intimate partner violence (IPV) are longstanding. Yet the role that measurement plays in how we understand the distribution of IPV has been understudied. We investigated whether people respond differently to IPV items by sex and sexual identity and the implications this has for understanding differences in IPV burdens. Our sample was 2,412 randomly selected residents of Toronto, Canada, from the Neighborhood Effects on Health and Well-being (NEHW) study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
(72 reference statements)
1
5
0
Order By: Relevance
“…similarities between the two populations demographically (e.g., majority White, similar rates of foreign-born individuals), politically (e.g., multi-party democratic structure, protection of civil liberties, separation of powers), and rights afforded to LGBTQ+ individuals (e.g., marriage equality, anti-discrimination laws, military service). Similar to U.S. studies, a large survey of randomly selected residents of Toronto, Canada (Yakubovich et al, 2022) found that LGB women were at the highest risk of experiencing IPV. Also similar to studies of the U.S. LGBTQ+ community, Barrett and Pierre (2013) found that bisexual Canadians were at higher risk of experiencing IPV compared to gay and lesbian Canadians.…”
Section: International Researchsupporting
confidence: 62%
See 3 more Smart Citations
“…similarities between the two populations demographically (e.g., majority White, similar rates of foreign-born individuals), politically (e.g., multi-party democratic structure, protection of civil liberties, separation of powers), and rights afforded to LGBTQ+ individuals (e.g., marriage equality, anti-discrimination laws, military service). Similar to U.S. studies, a large survey of randomly selected residents of Toronto, Canada (Yakubovich et al, 2022) found that LGB women were at the highest risk of experiencing IPV. Also similar to studies of the U.S. LGBTQ+ community, Barrett and Pierre (2013) found that bisexual Canadians were at higher risk of experiencing IPV compared to gay and lesbian Canadians.…”
Section: International Researchsupporting
confidence: 62%
“…Psychological and physical disabilities were also found to be associated with a greater risk of experiencing IPV in this sample. Like the Australian participants in Bourne et al's (2023) study, Yakubovich et al (2022) found that individuals were more likely to endorse specific experiences consistent with IPV than they were to acknowledge that they had experienced IPV.…”
Section: International Researchmentioning
confidence: 93%
See 2 more Smart Citations
“…We also did not explore gender identity, as this had not been asked about by age 21. Exploring IPVA patterns by sexual orientation and gender identity in-depth would be an important separate enquiry, given that previous research has highlighted different IPVA patterns and perceptions of IPVA among these groups ( Dickerson-Amaya & Coston, 2019 ; Yakubovich et al, 2021 ). In our qualitative work, we have captured the experiences of socio-economically deprived individuals and ethnic and sexual orientation minorities, which is being used to inform as to how different experiences of different types, severity and frequency of IPVA, and its impact might be for these groups, compared to those reported in the current study.…”
Section: Discussionmentioning
confidence: 99%